Debates—Hypothesis testing in hydrology: Pursuing certainty versus pursuing uberty. Issue 3 (29th March 2017) - Baker, Victor R.
Abstract: Modern hydrology places nearly all its emphasis on science‐as‐knowledge, the hypotheses of which are increasingly expressed as physical models, whose predictions are tested by correspondence to quantitative data sets. Though arguably appropriate for applications of theory to engineering and applied science, the associated emphases on truth and degrees of certainty are not optimal for the productive and creative processes that facilitate the fundamental advancement of science as a process of discovery. The latter requires an investigative approach, where the goal is uberty, a kind of fruitfulness of inquiry, in which the abductive mode of inference adds to the much more commonly acknowledged modes of deduction and induction. The resulting world‐directed approach to hydrology provides a valuable complement to the prevailing hypothesis‐ (theory‐) directed paradigm. Plain Language Summary: This commentary suggests that a world‐directed, investigative approach to hydrology may serve as a productive complement to the prevailing hypothesis‐ (theory‐) directed, approaches. The emphasis of the former on discovery has the potential to be transformative for investigative hydrology. Key Points: Modern hydrology places nearly all its emphasis on science‐as‐knowledge Such emphasis is contrary to the productive and creative processes that facilitate fundamental advances in science as a process of discovery Discovery occurs via investigation whereby abduction leads to uberty, a kind of fruitfulness of inquiry, followed by deduction and induction